2008
DOI: 10.1016/j.cub.2008.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Breaking Polarization Driven by a Cdc42p GEF-PAK Complex

Abstract: Summary Background In 1952, Alan Turing suggested that spatial patterns could arise from homogeneous starting conditions by feedback amplification of stochastic fluctuations. One example of such self-organization, called symmetry breaking, involves spontaneous cell polarization in the absence of spatial cues. The conserved GTPase Cdc42p is essential for both guided and spontaneous polarization, and in budding yeast cells Cdc42p concentrates at a single site (the presumptive bud site) at the cortex. Cdc42p con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
276
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(290 citation statements)
references
References 40 publications
10
276
2
2
Order By: Relevance
“…Moreover, a recent biochemical analysis demonstrated that Pak interferes with the ability of an exchange factor beta-PIX to activate Rac (ten Klooster et al, 2006), suggesting a function for Pak as an upstream inhibitor of Rac function. Our analysis also fits with the observation that Paks can act downstream of Cdc42 to modulate Rac activation, without their being absolutely required for lamellipodial formation (Cau and Hall, 2005), with observations suggesting that Cdc42 inhibits Pak activity (Weisz Hubsman et al, 2007), and by the presence of both Pak and Cdc42 in a single complex that regulates polarity in yeast (Kozubowski et al, 2008). The effects of Paks on changes in the direction of cell migration, e.g., during neural growth cone turning (Ang et al, 2003;Hing et al, 1999;Newsome et al, 2000), may reflect a similar function for Paks in damping local actin polymerization to facilitate the necessary redistribution of actin filaments.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, a recent biochemical analysis demonstrated that Pak interferes with the ability of an exchange factor beta-PIX to activate Rac (ten Klooster et al, 2006), suggesting a function for Pak as an upstream inhibitor of Rac function. Our analysis also fits with the observation that Paks can act downstream of Cdc42 to modulate Rac activation, without their being absolutely required for lamellipodial formation (Cau and Hall, 2005), with observations suggesting that Cdc42 inhibits Pak activity (Weisz Hubsman et al, 2007), and by the presence of both Pak and Cdc42 in a single complex that regulates polarity in yeast (Kozubowski et al, 2008). The effects of Paks on changes in the direction of cell migration, e.g., during neural growth cone turning (Ang et al, 2003;Hing et al, 1999;Newsome et al, 2000), may reflect a similar function for Paks in damping local actin polymerization to facilitate the necessary redistribution of actin filaments.…”
Section: Discussionsupporting
confidence: 86%
“…1). Interestingly, analogous studies in yeast have implicated Paks in the regulation of actin cytoskeletal polarity (Kozubowski et al, 2008). For example, germinating budding yeast cells lacking the Pak homolog Cla4 are unable to remodel their highly polarized actin cytoskeleton to undergo the normal switch from polar to isotropic growth (Kono et al, 2005), while Pak homolog Shk1/Orb6 in fission yeast cells is required for the switch from monopolar to bipolar growth (Sawin et al, 1999), and functions as part of a feedback loop in which polarized cytoskeletal organization helps to determine cell shape.…”
Section: Discussionmentioning
confidence: 91%
“…Most have focused on positive feedback loops at the front of cells involving a number of specific signaling molecules, such as RhoGTPases and PI3K, and a global inhibitory component that prevents activity at multiple sites (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). An increasing number of studies have implicated events at the cell rear, such as the local inhibition of signaling activities and force generation through actin depolymerization or Myosin II (78)(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%
“…In the budding yeast Saccharomyces cerevisiae, cells develop only a single polarized site through a winner-take-all mechanism during bud emergence (Irazoqui et al, 2003;Kozubowski et al, 2008;Slaughter et al, 2009a;Wedlich-Soldner et al, 2004). However, a winner-take-all mechanism cannot explain how cells develop multiple polarized sites often observed in higher eukaryotes.…”
Section: Introductionmentioning
confidence: 99%